Two new species of Curculionichthys (Siluriformes: Loricariidae) from the rio Amazonas basin, Brazil - Roxo, Fábio F. [UNESP]; Dias, Angelica C. [UNESP]; Silva, Gabriel S. C. [UNESP]; Oliveira, Claudio [UNESP] (Magnolia Press, 2017)
In the present study, we describe two new species of Curculionichthys from rio Tapajós and rio Tocantins basins in Brazil. Both species present all diagnostic features of Curculionichthys. Furthermore, both species C.Tukana and C. itaim are dis-Tinguished from congeners by the combination of seven characters: (1) a higher number of plates in abdominal lateral plates series; (2) the absence of large conspicuous odontodes forming rows on head and trunk; (3) the anterior profile of the head pointed; (4) a higher number of dentary teeth; (5) the lack of contrasting dark spots at the anterodorsal region of body; (6) the absence of an irregular concentration of chromatophores that entirely cover the anal-fin origin and adjacent region, and distal portion of the first unbranched anal-fin ray; and (7) the presence of odontodes forming aligned rows, more evident in the dorsal portion of head and in the lateral portion of caudal peduncle. Furthermore, C.Tukana can be further distinguished from congeners by three characters: (1) the papillae aligned in series that extends from the distal por-Tion of lower lip to dentary; (2) the absence of dark-brown spots scattered over the body; and (3) a higher number of max-illary teeth. The species C. itaim also can be further distinguished from congeners by five characters: (1) the papillae randomly distributed throughout the lower lip; (2) a smaller number of medial plates series on lateral portion of the body following the lateral line; (3) a smaller number of median plates series in abdomen; (4) the absence of dark-brown spots scattered over the body; and (5) the absence of one unpaired platelet on the dorsal portion of the caudal peduncle.
Keywords: Cascudinhos; Catfishes; Neotropical Region; Otothyrini; Taxonomy